LITERASI MANAJEMEN KEUANGAN SEDERHANA PADA UMKM KELURAHAN PATAM LESTARI - Ompusunggu, Hermaya; Husda, Anggun Permata; Rustam, Triana Ananda (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The presence of financial technology (fintech) in Indonesia helps micro, small and medium enterprises (MSMEs) in developing their businesses. Increased access to the world of banking has made MSME business easier. However, the limited ability of MSME players to apply fintech hinders its spread. "Fintech is a technological innovation aimed at complementing and facilitating financial transactions in society. The existence of fintech will make it easier for people to access various products in the financial sector and facilitate transactions and increase financial literacy. "MSMEs in Indonesia contribute 60% of the country's economy and absorb 97% of the workforce. However, even though there are more than 60 million MSMEs in Indonesia, only 12% can get financing or business capital loans from banks. This is where the role of fintech comes to help MSMEs,". Simple financial management literacy with an approach to financial technology is very relevant to current conditions. One of the applications of financial management with financial technology is as a medium for investing in stocks, where currently using smartphones significantly increases the efficiency of stock investment activities compared to conventional investment methods. The target participants in community service activities are MSME actors in the Patam Lestari Village area. The reason for choosing MSMEs is that currently the condition is being hit by the Covid19 pandemic, it has an impact on the economy of society in general and the buying and selling process of MSMEs in particular. The methods used in community service are counseling, question and answer, and practice methods. The results of the training received a good response from the participants. This can be seen from the results of the questionnaire that was distributed, there were 85% of participants who strongly agreed that the topics discussed were in accordance with the participants' expectations, 87% of participants strongly agreed that the material presented by the speaker was clear, and 89% of participants strongly agreed that the speaker mastered the topic presented.